Literatura e resistência. - Monteiro, Pedro Meira (Luso-Brazilian Review, 2013)
This article aims at putting Alfredo Bosi's work in dialogue with well-known theoretical trends in the English-speaking academia. I trace the steps I've taken to make some of Bosi's reflections available to an English-speaking audience, and raise a few questions: In the discussion on the "coloniality of power," which brings together "Postcolonial"and "Subaltern Studies", can Bosi's criticism play a role? What contribution can his "counter-ideological" critique make to an academic environment radically different from the one where it originated? Can a subaltern academic field speak? Finally, I focus on some of the founda-tions of Bosi's view and conclude with a discussion of the place of the margins in his thought, thus identifying what makes it at once distant from and close to a deconstructionist claim on the transitory nature of the subaltern subject.